Little monsters (2022) ebook - Lemire, Jeff (Little Monsters (2022), 2024)
They are the last children on Earth...who also happen to be vampires. For longer than they can remember, these child vampires have lived a life of eternal wonder amongst the ruins of humanity. But shocking events fracture the group and set them on a path of discovery that will shatter their innocence forever. Their ultimate survival depends on their ability to work together against the humans. It's Lord of the Flies meets vampires in an oversized deluxe hardcover volume of the bold series from JEFF LEMIRE and DUSTIN NGUYEN, the Eisner-winning creative team behind the bestselling DESCENDER and ASCENDER series. Collects the entire hit LITTLE MONSTERS series (#1-13)!